Modification of the microstructure of the films formed by gamma irradiated starch examined by SEM. (January 2016) - Cieśla, K.; Sartowska, B.
Abstract: The paper concerns the effect of gamma irradiation carried out for starch on the microstructure of the films prepared using the starch and its composition with sodium laurate (NaLau) and cetyltrimethylammonium bromide (CTAB) studied by scanning electron microscopy (SEM). Potato starch was irradiated with 60 Co gamma rays applying a dose of 30 kGy. Films were prepared by the solution casting method with the addition of 30 wt% glycerol as a plasticizer. Films containing NaLau and CTAB were prepared after performing the procedure, leading to starch–surfactant complexes. Mechanical tests and wetting angle measurements were performed for the films. SEM observations were carried out for the surfaces, fractures and/or sections of the films subjected to chemical fixation and for the dried films. The films obtained using irradiated starch are characterized by a smoother and more homogeneous structure as compared to those based on the non-irradiated starch. Besides, a number of small precipitates were observed on the films surfaces after drying and the number of those precipitates seemed to be higher after irradiation. The results can be related to differences in the microstructure of gels formed on the intermediate step of the films preparation and to the presence of two phases in the system and might serve for explanation of the radiation induced improvement of the hydrophilic/hydrophobic properties, a modification of the mechanical properties of the films, as well as for the changes of those properties resulting after storage. Highlights: Changes of the mechanical properties and hydrophobicity occur due to irradiation. SEM studies were conducted for the chemically fixed and for the dried films. The films microstructures project partially those of the former gels. The improvement of the films homogeneity occurs due to irradiation. Phase separation occurs during storage and is facilitated after irradiation.